Adaptive sliding mode Gaussian controller for artificial pancreas in TIDM patient. (November 2017) - Patra, Akshaya Kumar; Rout, Pravat Kumar
Graphical abstract: Highlights: Developing of a SIMULINK model for BG regulation in TIDM patient. Design of artificial pancreas based on the SMGC/SE to regulate BG levels. Kalman filter is integrated into the controller to enhance the control performance. Evaluating the control performance under the process and sensor noise. The comparative analysis has been done to justify the control performance. Abstract: Optimal closed loop control of blood glucose (BG) level has been a major focus for the past so many years to realize an artificial pancreas for type-I diabetes mellitus (TIDM) patients. There is an urgency for controlled drug delivery system to design with appropriate controller not only to regulate the BG level, but also for other chronic clinical disorders requiring continuous long term medication. As a solution to the above problem, a novel sliding mode Gaussian controller with state estimation (SMGC/SE) is proposed, whose gains dynamically vary with respect to the error signal. For the designing of the SMGC/SE, a nonlinear TIDM patient model is linearized as a 9th order state-space model with a micro-insulin dispenser. This controller is evaluated and compared with other recently published control techniques. Obtained results clearly reveal the better performance of the proposed method to regulate the BG level within the normoglycaemic range in terms of accuracy and robustness.